Ototoxic Effect of Topical Ciclopirox as an Antimycotic Preparation - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2008)
Objective: To evaluate the ototoxicity of ciclopirox-containing solution as an otologic preparation for the treatment of otomycosis. Background: Ciclopirox is a synthetic antimycotic agent available in a variety of formulations to treat superficial fungal infections. Ciclopirox has demonstrated both fungicidal and fungistatic activity in vitro against a broad spectrum of pathogenic fungi. It also possesses a broad-spectrum antibacterial properties, anti-inflammatory, and antiedema effect. The ototoxic effect of ciclopirox-containing solutions has not been known, so the current study was designed to observe the ototoxic effect of this solution experimentally. Materials and Methods: Experiments were performed in 22 young male albino guinea pigs (weight, 450-550 g). The 10 animals in the experimental group received ciclopirox solution, and the control group was divided into two groups of six animals each. The first group received saline solution (negative control) and the second received gentamicin (40 mg/mL; ototoxic control). Under general anesthesia, pretreatment auditory brainstem responses (ABRs) from the right cars were obtained from the animals in all groups. The right tympanic membranes were totally perforated, and a small piece of Gelfoam was applied to the middle ear directly to the round window membrane. Ear solutions were applied through transcanal approach to the middle ear twice a day in 2 weeks. Twenty-two animals of perforated tympanic membrane were observed during a 2-week period. Posttreatment ABRs were obtained in all groups in a week after the last administration. Results: Baseline ABR results were normal in right ears of all animals tested. Animals undergoing placement of Gelfoam with either ciclopirox solution or saline in the middle ear showed no changes in the ABR threshold. The gentamicin Group showed a significant change in the ABR threshold. Conclusion: In the guinea pig, when applied topically to the middle ear, ciclopirox does not cause a reduction in the ABR threshold. Because its safety has not yet been confirmed in patients, caution should be observed when prescribing this agent.
Keywords: Auditory brainstem responses; Ciclopirox; Ototoxicity; MIDDLE-EAR; OTOMYCOSIS